Deradicalization through Revitalization of Religious and Nationality Insights among Indonesian Students - Muhammad Turhan Yani; Yusuf Hanafi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Radicalism remains a latent ideology capable of growing and developing in various settings, including higher education institutions. This study explores the phenomenon of radicalization among University students, emphasizing the infiltration of radical ideologies and the role of Islamic education lecturers in countering this trend. The research employs a qualitative approach, utilizing in-depth interviews conducted over three months with lecturers from seven universities in East Java, Indonesia. The findings reveal that while numerous studies have labeled universities as breeding grounds for radicalism, the situation in the field indicates a more nuanced reality. Radicalization on campuses persists, yet efforts to counteract it through religious and national identity revitalization have been effective. Islamic education lecturers play a critical role in fostering religious moderation, promoting Islam Rahmatan lil ‘Alamin, and restructuring campus mosques to prevent infiltration by radical preachers. This study underscores the importance of strengthening national and religious awareness in university settings to mitigate the spread of radicalism. It also highlights the need for institutional policies and community engagement to sustain deradicalization efforts. The findings contribute to the broader discourse on counter radicalization in higher education and offer practical implications for educational institutions and policymakers in fostering inclusive and tolerant academic environments.